Alcohol consumption is positively associated with fasting serum ghrelin in non-dependent adults: Results from the population-based LIFE-Adult-Study. - Wittekind, D. A.; Kratzsch, J.; Mergl, R.; Enzenbach, C.; Witte, A. V.; Villringer, A.; Kluge, M. (Psychoneuroendocrinology, 2018)
BACKGROUND: Animal experiments and studies in alcohol dependent patients indicate that ghrelin signaling in the brain is causally involved in the regulation of alcohol reward and intake. Increasing ghrelin levels enhances alcohol craving and intake, blocking ghrelin receptors abolishes these effects. If ghrelin is also involved in non-dependent alcohol consumption in humans, though, remains unknown. The aim was therefore to investigate the relationship between ghrelin serum levels and alcohol consumption in a large population-based sample. METHODS: Total ghrelin was determined after an overnight fast in 1666 subjects participating in a population-based cross-sectional study ('LIFE') including 10,000 adults. 1521 subjects were included in this analysis. Alcohol consumption was assessed using a food frequency questionnaire (FFQ). Multiple linear regression analyses and extreme group comparisons testing for statistical differences of alcohol consumption between the highest and lowest quartile according to ghrelin levels were performed. RESULTS: Alcohol consumption was positively associated with serum ghrelin; total sample: beta = 0.003, p = 0.002; men: beta = 0.005, p = 0.023; women: beta = 0.002, p = 0.007, adjusted for age, BMI and smoking status. Mean alcohol consumption in men/women belonging to the highest quartile of serum ghrelin levels (men: 21.5 (21.1) g/day; women: 7.5 (11.4) g/day) was considerably higher than in those belonging to the lowest quartile (men: 16.5 (19.3) g/day p < 0.002; women: 4.59 (10.7) g/day p = 0.0001). CONCLUSION: This is the first study showing that alcohol consumption is positively associated with serum ghrelin in a population-based sample. The study provides an initial indication that ghrelin is also involved in the regulation of alcohol consumption in non-dependent subjects.
Keywords: Adolescent; Adult; Alcohol Drinking/*metabolism; Cross-Sectional Studies; Female; Germany; Ghrelin/*analysis/blood; Humans; Male; Receptors, Ghrelin/metabolism; Regression Analysis